Magnoflorine ameliorates hepatic fibrosis and hepatic stellate cell activation by regulating ferroptosis signaling pathway - Meiling Zhang; Lenan Xu; Chengkai Zhu; Yawen Zhang; Ruixiang Luo; Juan Ren; Jie Yu; Yanmei Zhang; Guang Liang; Yi Zhang (Heliyon)
Liver fibrosis is a chronic liver disease that brings a heavy economic burden to the world and has attracted global attention. Although the pathological mechanisms and treatment strategies of liver fibrosis have been extensively studied, there are currently no effective targeted drugs for the prevention and treatment of liver fibrosis in clinical practice. Therefore, it is imperative to seek and develop effective treatment strategies and drugs for liver fibrosis. Magnoflorine (MAG) is a natural product with multiple pharmacological activities. Thus, in this study, we will explore the effect of MAG on alleviating liver fibrosis in mice and its mechanism of action. Our study indicates that MAG can alleviate liver damage, improve liver collagen deposition, and significantly reduced the expression levels of hepatic stellate cells (HSCs) activation markers in vivo. Additionally, the findings of this study indicate that MAG can inhibit the transforming growth factor-beta (TGF-β)/Smad signaling pathway. Bioinformatics analysis suggests that the alleviating effect of MAG on liver fibrosis may be associated with ferroptosis. Interestingly, in vitro experiments have demonstrated that MAG slows down the progression of liver fibrosis by inhibiting the activation of HSCs, and further confirms that MAG promotes ferroptosis in ROS-mediated activated HSCs. In short, MAG has a good alleviating effect on liver fibrosis and will be a potential candidate drug for the treatment of liver fibrosis.